Regime Shift : Comparative Dynamics of the Japanese Political Economy - Pempel, T. J., 1942- (Book collections on Project MUSE., 1998)
The Liberal Democratic Party, which dominated postwar Japan, lost power in the early 1990s. During that same period, Japan's once stellar economy suffered stagnation and collapse. Now a well-known commentator on contemporary Japan traces the political dynamics of the country to determine the reasons for these changes and the extent to which its political and economic systems have been permanently altered. T.J. Pempel contrasts the political economy of Japan during two decades: the 1960s, when the nation experienced conservative political dominance and high growth, and the early 1990s, when the "bubble economy" collapsed and electoral politics changed. The different dynamics of the two periods indicate a regime shift in which the present political economy deviates profoundly from earlier forms. This shift has involved a transformation in socioeconomic alliances, political and economic institutions, and public policy profile, rendering Japanese politics far less predictable than in the past. Pempel weighs the Japanese case against comparative data from the United States, Great Britain, Sweden, and Italy to show how unusual Japan's political economy had been in the 1960s. Regime Shift suggests that Japan's present troubles are deeply rooted in the economy's earlier success. It is a much-anticipated work that offers an original framework for understanding the critical changes that have affected political and economic institutions in Japan